Biosynthesis and Comprehensive Structural Characterization of TiO₂-Loaded Bentonite Nanocomposites using Orange Peel Extract - Yahaya, Kabir M.; Sumaila, Abdulmumuni; Yahaya, Ruqayya A.; Abdulsalam, Sa’adatu; Jimoh, Ibrahim; Abdulkarim, Ibrahim; Sumaila, Ahmed O.; Yusuf, Ruqayyah O. (Journal of Science Research and Reviews, 2025)
Increasing contamination of water resources by industrial effluents has necessitated the development of low-cost, eco-friendly, and efficient materials for wastewater treatment. Among such materials, titanium dioxide (TiO₂) is recognized for its excellent photocatalytic activity, while bentonite clay provides high surface area and strong adsorption capacity. This study reports a green biosynthesis route for TiO₂-loaded bentonite nanocomposites (BTNCs) using orange peel extract as a natural reducing and stabilizing agent to integrate the photocatalytic and adsorptive properties of TiO₂ and bentonite respectively. Characterization of the synthesized nanocomposites was carried out using a suite of analytical techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. Characterization via XRD, SEM, and Raman spectroscopy confirmed the successful incorporation of anatase TiO₂ nanoparticles ( 17.5 nm) uniformly dispersed within the bentonite matrix, with evidence of Ti–O–Si bond formation indicating strong interaction between TiO₂ and bentonite. The eco-friendly synthesis method discourages the use of toxic reagents and offers multifunctional nanomaterials with promising applications in photocatalytic wastewater treatment.